The development of biophysical models of the electrically stimulated auditory nerve: Single-node and cable models. (2nd July 2016) - O'Brien, Gabrielle E.; Rubinstein, Jay T.
ABSTRACT: In the last few decades, biophysical models have emerged as a prominent tool in the study and improvement of cochlear implants, a neural prosthetic that restores a degree of sound perception to the profoundly deaf. Owing to the spatial phenomena associated with extracellular stimulation, these models have evolved to a relatively high degree of morphological and physiological detail: single-node models in the tradition of Hodgkin–Huxley are paired with cable descriptions of the auditory nerve fiber. No singular model has emerged as a frontrunner to the field; rather, parameter sets deriving from the channel kinetics and morphologies of numerous organisms (mammalian and otherwise) are combined and tuned to foster strong agreement with response properties observed in vivo, such as refractoriness, summation, and strength–duration relationships. Recently, biophysical models of the electrically stimulated auditory nerve have begun to incorporate adaptation and stochastic mechanisms, in order to better realize the goal of predicting realistic neural responses to a wide array of stimuli.